Naiza Khan - Khan, Nazia H. (Hong Kong, 2013)
Although the multidimensional quality and slow, at times errant, unfolding of Naiza Khan$1 (Bs work, along with her unfashionable insistence on (3z(Bthe importance of gesture [with] a certain level of randomness,(3y (B[2] creates a sense of being out-of-time, or at least of standing on the edge, outside the current concerns of either daily life or the art world. Actually, her choice of the city of Karachi (and the small island of Manora, just off its coast), as subjects for her work is far from peripheral and very much engaged with the world around around her. The stories of both places, developeds
Keywords: contemporary art -- Pakistan; Artists Pakistan Exhibitions; Art work; Essays and interviews